AlN / Si3N4 composite ceramic substrate and preparation method and application thereof
Through the preparation method of AlN/Si3N4 composite ceramic substrate, combined with EuO2-HfO2 powder catalyst and casting process, the challenges of mechanical and thermal conductivity of ceramic substrates in highly integrated power systems are solved, and a high-performance composite ceramic substrate is achieved.
Patent Information
- Application Number
- CN202411954239.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing ceramic substrates are difficult to meet the strict requirements of mechanical properties and thermal conductivity in highly integrated, miniaturized and intelligent power systems, especially in the challenges of combining the mechanical properties advantages of silicon nitride materials with the thermal conductivity of aluminum nitride materials.
Using the preparation method of AlN/Si3N4 composite ceramic substrate, the Si-based casting slurry and the Al2O3-C casting slurry are filled and sintered after the casting process, and combined with EuO2-HfO2 powder as a catalyst, nitriding is carried out to form an interlocking dense bimodal microstructure and thermal conduction path.
The AlN/Si3N4 composite ceramic substrate has excellent mechanical properties and thermal conductivity, with a relative density of more than 97%, a flexural strength of 687~860MPa, a fracture toughness of 6.4~8.7MPa·m1/2, and a thermal conductivity of 86~116W m-1K-1, which is suitable for automotive electronics or aerospace fields.
Smart Images

Figure CN119797930A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material production, and more specifically, relates to an AlN / Si3N4 composite ceramic substrate and a preparation method and application thereof. Background Art
[0002] At present, in order to more effectively control and utilize electricity, ceramic substrates have been widely used in various fields such as new energy vehicles, high-speed railways, robots, and aerospace. However, the power systems in the above fields are currently developing towards high integration, miniaturization, and intelligence, which puts more stringent requirements on ceramic substrates as supporting elements and heat sinks, especially for the mechanical properties and thermal conductivity of ceramic substrates. Therefore, there is an urgent need for a method that can efficiently produce ceramic substrates that take into account both mechanical properties and thermal conductivity.
[0003] Silicon nitride ceramic materials have long been used in aerospace, automotive, chemical, and civil fields due to their excellent mechanical properties, such as high strength and high toughness, as well as corrosion resistance, wear resistance, excellent dielectric constant, and chemical stability. Aluminum nitride ceramic materials have excellent thermal conductivity and electrical insulation, and are widely used in electronic device substrates, heat sinks, and lasers. How to combine the mechanical properties of silicon nitride materials with the excellent thermal conductivity of aluminum nitride materials to prepare high-strength and high-thermal-conductivity composite ceramic substrates is a technical issue worthy of our in-depth study. Summary of the invention
[0004] In order to solve the above-mentioned deficiencies and shortcomings of the prior art, the primary purpose of the present invention is to provide an AlN / Si3N4 composite ceramic substrate. The composite ceramic has excellent mechanical properties and thermal conductivity.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned AlN / Si3N4 composite ceramic substrate.
[0006] Another object of the present invention is to provide an application of the above-mentioned AlN / Si3N4 composite ceramic substrate.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] An AlN / Si3N4 composite ceramic substrate is prepared by mixing Si powder, EuO2-HfO2 powder, MgO powder, Yb2O3 powder, polyethylene glycol butyral, polyethylene glycol and anhydrous ethanol through ball milling to obtain Si-based tape-casting slurry; mixing Al2O3 powder, C powder, Yb2O3 powder, polyethylene glycol butyral, polyethylene glycol and anhydrous ethanol through ball milling to obtain Al2O3-C tape-casting slurry; and subjecting the Si-based tape-casting slurry to a tape-casting process in a mold to obtain a Si-based ceramic sheet with n×m matrix circular holes. Al2O3-C casting slurry is filled into the circular holes of Si-based ceramic blank to obtain Si-Al2O3-C composite ceramic blank; the composite ceramic blank is placed in a gas pressure sintering furnace, a mixed gas of N2 and H2 is introduced at 800-1000°C under a vacuum state, then a nitridation treatment is performed at 1320-1380°C, and then 4-6MPa flowing N2 is introduced, the temperature is raised to 1600-1800°C for insulation, then the temperature is lowered to 800-1000°C, and the composite ceramic blank is naturally cooled to room temperature to obtain the product.
[0009] Preferably, the purity of the Si powder, EuO2 powder, HfO2 powder, MgO powder, Yb2O3 powder, Al2O3 powder and C powder is above 99.9%, the particle size of the Si powder is 0.5-1μm; the particle sizes of the EuO2 powder, HfO2 powder, MgO powder and C powder are all <100nm; the particle sizes of the Yb2O3 powder and Al2O3 powder are both 1-2μm.
[0010] Preferably, the mass ratio of the Si powder: EuO2-HfO2 powder: MgO powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol is (88-92):(2-6):2:4:10:10:200, wherein the mass ratio of EuO2 powder and HfO2 powder is 1:1; the mass ratio of the Al2O3 powder: C powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol is (76-80):(16-20):4:10:10:200.
[0011] Preferably, the mold is a matrix of n×m Cylinder, wherein n=[a / 30], m=[b / 30], a is the total length of the composite ceramic substrate, b is the total width of the composite ceramic substrate; 100mm≤a≤300mm, 50mm≤b≤200mm.
[0012] Preferably, the volume ratio of N2 to H2 in the mixed gas is (93-97):(3-7).
[0013] Preferably, the relative density of the AlN / Si3N4 composite ceramic substrate is above 97%, the bending strength is 687-860 MPa, and the fracture toughness is 6.4-8 MPa·m 1 / 2, hardness is 15.6~17GPa, thermal conductivity is 86~116W m -1 K -1 .
[0014] The preparation method of the AlN / Si3N4 composite ceramic substrate comprises the following steps:
[0015] S1. Si powder, EuO2-HfO2 powder, MgO powder, Yb2O3 powder, polyethylene glycol butyral, polyethylene glycol and anhydrous ethanol were mixed by ball milling to obtain a Si-based tape casting slurry;
[0016] S2. Al2O3 powder, C powder, Yb2O3 powder, polyethylene glycol butyral, polyethylene glycol and anhydrous ethanol were mixed by ball milling to obtain Al2O3-C casting slurry;
[0017] S3. After the Si-based tape casting slurry is subjected to a tape casting process in a mold, an n×m matrix is obtained. A Si-based ceramic sheet with circular holes; filling the Al2O3-C tape-casting slurry into the circular holes of the Si-based ceramic sheet to obtain a Si-Al2O3-C composite ceramic sheet;
[0018] S4. Place the Si-Al2O3-C composite ceramic sheet into a gas pressure sintering furnace, raise the temperature to 800-1000°C under vacuum, then introduce a mixed gas of N2 and H2, then raise the temperature to 1320-1380°C and keep it for 2-3 hours for nitridation treatment, then introduce 4-6MPa flowing N2, raise the temperature to 1600-1800°C and keep it for 3-4 hours, then lower the temperature to 800-1000°C, and after it is naturally cooled to room temperature, obtain the AlN / Si3N4 composite ceramic substrate.
[0019] Preferably, the casting process conditions described in step S3 are: casting belt speed is 0.3-3 m / min; green body thickness is 0.3-0.7 mm; drying temperature is 60-80° C.; and drying time is 3-5 h.
[0020] Preferably, in step S4, the rate of heating to 800-1000°C is 18-25°C / min, the rate of heating to 1320-1380°C is 15-18°C / min, and the rate of heating to 1600-1800°C is 8-12°C / min.
[0021] The AlN / Si3N4 composite ceramic substrate is used in the fields of automotive electronics or aerospace.
[0022] The present invention places the Si-Al2O3-C composite ceramic sheet into a gas pressure sintering furnace and maintains vacuum. After the temperature is raised to 800-1000°C, a mixed atmosphere of N2 (95 vol%) and H2 (5 vol%) is introduced, and then the temperature is raised to 1320-1380°C and kept warm for 2-3 hours. During this process, EuO2-HfO2 powder in the Si-Al2O3-C composite ceramic sheet acts as a catalyst to promote the nitridation of Si powder into α-Si3N4, thereby ensuring the nitridation quality and shortening the nitridation time; and the temperature is raised to 1600-1800°C and kept warm for 3-4 hours. On the one hand, α-Si3N4 undergoes liquid phase sintering, and the phase change of α→β-Si3N4 and the growth of β-Si3N4 grains proceed synchronously, forming an interlocking dense double-peak microstructure. On the other hand, at 1600-1800°C, Al2O3 powder undergoes a carbon thermal reduction reaction:
[0023] Al2O3(s)+C(s)→AlN(s)+CO(g)
[0024] The removal of the circular hole area C and the preparation of AlN ceramics are achieved. It is worth noting that at the intersection of the circular holes between AlN and Si3N4 in the AlN / Si3N4 composite ceramic substrate, the following reactions occur at a temperature of 1600-1800°C:
[0025] 3Al2O3(s)+3C(s)+4Si3N4(s)+N2(g)→3Si4Al2O3N6(s)+3CO(g)
[0026] A 0.3-0.5 mm circular β-Sialon phase transition region was generated, which further tightly connected the AlN and Si3N4 ceramics, while balancing the thermal stress caused by the difference in thermal expansion coefficients of different materials, ensuring the molding and densification of the composite ceramic substrate, and producing a high-performance AlN / Si3N4 composite ceramic substrate.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The Si3N4 ceramics in the present invention form an interlocking dense double-peak microstructure, which ensures that the AlN / Si3N4 composite ceramic substrate has excellent mechanical properties; at the same time, the formation of the matrix AlN ceramics enables the composite ceramic substrate to have a thermal conductive path with good thermal conductivity, thereby achieving optimized comprehensive performance.
[0029] 2. In the AlN / Si3N4 composite ceramic substrate of the present invention, a 0.3-0.5 mm circular β-Sialon phase transition region is formed at the junction of the circular holes of AlN and Si3N4, which not only further closely connects the AlN and Si3N4 ceramics, but also balances the thermal stress caused by the difference in thermal expansion coefficients of AlN and Si3N4, thereby ensuring the molding and density of the composite ceramic substrate.
[0030] 3. The present invention promotes the nitridation of Si powder by introducing Si powder into EuO2-HfO2 powder, thereby ensuring the nitridation quality, shortening the nitridation time, simplifying the preparation process, and eliminating the need for separate debinding and decarbonizing steps, thereby saving time and cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the production process of the AlN / Si3N4 composite ceramic substrate of the present invention.
[0032] Figure 2 It is a schematic diagram of the mold of the cylinder having an n×m matrix according to the present invention.
[0033] Figure 3 The present invention has an n×m matrix Schematic diagram of the casting process of Si-based ceramic sheets with round holes. DETAILED DESCRIPTION
[0034] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0035] The present invention uses Si powder (purity of more than 99% and particle size of 0.5 to 1 μm), EuO2 powder (purity of more than 99.99% and particle size of <100nm), HfO2 powder (purity of more than 99.99% and particle size of <100nm), MgO powder (purity of more than 99.9% and particle size of <100nm), Yb2O3 powder (purity of more than 99.99% and particle size of 1 to 2 μm), Al2O3 powder (purity of more than 99.99% and particle size of 1 to 2 μm), C powder (purity of more than 99.99% and particle size of <100nm), and Yb2O3 powder (purity of more than 99.99% and particle size of 1 to 2 μm).
[0036] Example 1
[0037] 1. Mix Si powder: EuO2-HfO2 powder (the mass ratio of EuO2 powder to HfO2 powder is 1:1): MgO powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol in a mass ratio of 90:4:2:4:10:10:200 and ball-mill to obtain a Si-based tape-casting slurry;
[0038] 2. Place the Si-based tape casting slurry into a matrix with (15-20)×(9-12) Cylinder mold (such as Figure 2 After the casting process (casting belt speed is 0.3-3 m / min; green body thickness is 0.3-0.7 mm; drying temperature is 60-80° C.; drying time is 3-5 h), the 5×3 matrix is obtained by cutting and separation. The process is as follows: Figure 3 As shown;
[0039] 3. Mix Al2O3 powder: C powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol in a mass ratio of 78:18:4:10:10:200 and ball-mill to obtain Al2O3-C tape-casting slurry; fill the Al2O3-C tape-casting slurry into the circular holes of the Si-based ceramic sheet to obtain a Si-Al2O3-C composite ceramic sheet;
[0040] 4. Put the Si-Al2O3-C composite ceramic sheet into a gas pressure sintering furnace, heat it to 800℃ at a rate of 20℃ / min under vacuum, then introduce a mixed gas of N2 (95vol%) and H2 (5vol%), heat it to 1340℃ at 16℃ / min and keep it for 3h for nitridation treatment, then heat it to 1800℃ at 12℃ / min and keep it for 3h. The N2 pressure is 5MPa during the heat preservation process. After heat preservation, cool it to 800℃ and wait for it to cool naturally to room temperature to obtain an AlN / Si3N4 composite ceramic substrate. Figure 1 shown.
[0041] The relative density of the AlN / Si3N4 composite ceramic substrate prepared in this embodiment is 98.2%, the bending strength is 860MPa, and the fracture toughness is 8.7MPa·m 1 / 2 , hardness is 16.4GPa, thermal conductivity is 112W m -1 K -1 The AlN / Si3N4 composite ceramic substrate has excellent mechanical properties (Si3N4 ceramic matrix) and thermal conductivity (AlN ceramic pathway).
[0042] Example 2
[0043] The difference from Example 1 is that in step 1, the mass ratio of Si powder: EuO2-HfO2 powder (the mass ratio of EuO2 powder and HfO2 powder is 1:1): MgO powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol is 92:2:2:4:10:10:200 and mixed and ball-milled to obtain Si-based tape casting slurry.
[0044] The relative density of the AlN / Si3N4 composite ceramic substrate prepared in this embodiment is 97.6%, the bending strength is 780MPa, and the fracture toughness is 7.2MPa·m 1 / 2 , hardness is 16.8GPa, thermal conductivity is 110W m -1 K -1 .
[0045] Example 3
[0046] The difference from Example 1 is that in step 1, the mass ratio of Si powder: EuO2-HfO2 powder (the mass ratio of EuO2 powder and HfO2 powder is 1:1): MgO powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol is 88:6:2:4:10:10:200 and mixed and ball-milled to obtain Si-based tape casting slurry.
[0047] The relative density of the AlN / Si3N4 composite ceramic substrate prepared in this embodiment is 97.4%, the flexural strength is 756MPa, and the fracture toughness is 7.18MPa·m 1 / 2 , hardness is 16.6GPa, thermal conductivity is 106W m -1 K -1 .
[0048] Example 4
[0049] The difference from Example 1 is that in step 2, the mass ratio of Al2O3 powder: C powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol is 76:20:4:10:10:200, and the mixed ball milling is carried out to obtain Al2O3-C casting slurry.
[0050] The relative density of the AlN / Si3N4 composite ceramic substrate prepared in this embodiment is 98.1%, the bending strength is 801 MPa, and the fracture toughness is 7.8 MPa·m 1 / 2 , hardness is 16.6GPa, thermal conductivity is 114W m -1 K -1 .
[0051] Example 5
[0052] The difference from Example 1 is that in step 2, the mass ratio of Al2O3 powder: C powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol is 80:16:4:10:10:200, and the mixed ball milling is carried out to obtain Al2O3-C casting slurry.
[0053] The relative density of the AlN / Si3N4 composite ceramic substrate prepared in this embodiment is 97.9%, the bending strength is 764MPa, and the fracture toughness is 7.2MPa·m 1 / 2 , hardness is 15.8GPa, thermal conductivity is 86W m -1 K -1 .
[0054] Example 6
[0055] The difference from Example 1 is that in step 3, the Si-based tape casting slurry is placed in a matrix having (15-20)×(9-12) After the cylindrical mold is subjected to the casting process (casting belt speed is 0.3-3 m / min; green body thickness is 0.3-0.7 mm; drying temperature is 60-80°C; drying time is 3-5 h), the 5×3 matrix is obtained by cutting and separating. A Si-based ceramic sheet (150 mm×90 mm) with a circular hole; Al2O3-C tape-casting slurry is filled into the circular hole of the Si-based ceramic sheet to obtain a Si-Al2O3-C composite ceramic sheet.
[0056] The relative density of the AlN / Si3N4 composite ceramic substrate prepared in this embodiment is 97.4%, the flexural strength is 687MPa, and the fracture toughness is 6.8MPa·m 1 / 2 , hardness is 16.8GPa, thermal conductivity is 116W m -1 K -1 .
[0057] Example 7
[0058] The difference from Example 1 is that in step 4, the Si-Al2O3-C composite ceramic sheet is placed in a gas pressure sintering furnace, and a mixed gas of N2 (95 vol%) and H2 (5 vol%) is introduced when the temperature is raised to 800°C at a rate of 20°C / min under vacuum, and the temperature is raised to 1340°C at 16°C / min and kept for 3 hours for nitridation treatment, and then the temperature is raised to 1600°C at 12°C / min and kept for 3 hours, and the N2 pressure is 5MPa during the heat preservation process. After the heat preservation, the temperature is lowered to 800°C, and after it is naturally cooled to room temperature, the AlN / Si3N4 composite ceramic substrate is obtained.
[0059] The relative density of the AlN / Si3N4 composite ceramic substrate prepared in this embodiment is 97.2%, the bending strength is 723 MPa, and the fracture toughness is 6.9 MPa·m 1 / 2 , hardness is 17GPa, thermal conductivity is 91Wm -1 K -1 .
[0060] Example 8
[0061] The difference from Example 1 is that in step 4, the Si-Al2O3-C composite ceramic sheet is placed in a gas pressure sintering furnace, and a mixed atmosphere of N2 (95 vol%) and H2 (5 vol%) is introduced when the temperature is raised to 800°C at a rate of 20°C / min under vacuum, and the temperature is raised to 1340°C at 16°C / min and kept for 3 hours for nitridation treatment, and then the temperature is raised to 1700°C at 12°C / min and kept for 3 hours, and the N2 pressure during the heat preservation process is 5MPa. After the heat preservation, the temperature is lowered to 800°C, and after it is naturally cooled to room temperature, the AlN / Si3N4 composite ceramic substrate is obtained.
[0062] The relative density of the AlN / Si3N4 composite ceramic substrate prepared in this embodiment is 97.9%, the bending strength is 749 MPa, and the fracture toughness is 7.3 MPa·m 1 / 2 , hardness is 16.1GPa, thermal conductivity is 103W m -1 K -1 .
[0063] The AlN / Si3N4 composite ceramic substrate prepared by the present invention has a relative density of more than 97%, a bending strength of 687-860 MPa, and a fracture toughness of 6.4-8.7 MPa·m 1 / 2 , thermal conductivity is 86~116W m -1 K -1 , indicating that the AlN / Si3N4 composite ceramic substrate has excellent mechanical properties (flexural strength and fracture toughness) and thermal conductivity, and can be used in automotive electronics or aerospace fields.
[0064] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An AlN / Si3N4 composite ceramic substrate, characterized in that: The composite ceramic substrate is prepared by mixing Si powder, EuO2-HfO2 powder, MgO powder, Yb2O3 powder, polyethylene glycol butyral, polyethylene glycol and anhydrous ethanol through ball milling to obtain Si-based tape casting slurry; mixing Al2O3 powder, C powder, Yb2O3 powder, polyethylene glycol butyral, polyethylene glycol and anhydrous ethanol through ball milling to obtain Al2O3-C tape casting slurry; subjecting the Si-based tape casting slurry to a tape casting process in a mold to obtain a Si-based ceramic sheet with n×m matrix circular holes; and subjecting the Al2 The O3-C cast slurry is filled in the circular holes of the Si-based ceramic sheet to obtain a Si-Al2O3-C composite ceramic sheet; the composite ceramic sheet is placed in a gas pressure sintering furnace, a mixed gas of N2 and H2 is introduced at 800-1000°C while maintaining a vacuum state, then a nitridation treatment is performed at 1320-1380°C, and then 4-6MPa of flowing N2 is introduced, the temperature is raised to 1600-1800°C for insulation, and then the temperature is lowered to 800-1000°C, and the product is obtained after it is naturally cooled to room temperature.
2. The AlN / Si3N4 composite ceramic substrate according to claim 1, characterized in that: The purity of the Si powder, EuO2 powder, HfO2 powder, MgO powder, Yb2O3 powder, Al2O3 powder and C powder is all above 99.9%, the particle size of Si powder is 0.5-1μm; the particle sizes of EuO2 powder, HfO2 powder, MgO powder and C powder are all <100nm; the particle sizes of Yb2O3 powder and Al2O3 powder are all 1-2μm.
3. The AlN / Si3N4 composite ceramic substrate according to claim 1, characterized in that: The mass ratio of Si powder: EuO2-HfO2 powder: MgO powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol is (88-92):(2-6):2:4:10:10:200, wherein the mass ratio of EuO2 powder and HfO2 powder is 1:1; the mass ratio of Al2O3 powder: C powder: Yb2O3 powder: polyethylene glycol butyral: polyethylene glycol: anhydrous ethanol is (76-80):(16-20):4:10:10:
200.
4. The AlN / Si3N4 composite ceramic substrate according to claim 1, characterized in that: The mold is a matrix of n×m Cylinder, wherein n=[a / 30], m=[b / 30], a is the total length of the composite ceramic substrate, b is the total width of the composite ceramic substrate; 100mm≤a≤300mm, 50mm≤b≤200mm.
5. The AlN / Si3N4 composite ceramic substrate according to claim 1, characterized in that: The volume ratio of N2 to H2 in the mixed gas is (93-97):(3-7).
6. The AlN / Si3N4 composite ceramic substrate according to claim 1, characterized in that: The relative density of the AlN / Si3N4 composite ceramic substrate is above 97%, the bending strength is 687-860MPa, and the fracture toughness is 6.4-8MPa·m 1 / 2 , hardness is 15.6~17GPa, thermal conductivity is 86~116W m -1 K -1 .
7. The method for preparing the AlN / Si3N4 composite ceramic substrate according to any one of claims 1 to 6, characterized in that: The steps include: S1. Si powder, EuO2-HfO2 powder, MgO powder, Yb2O3 powder, polyethylene glycol butyral, polyethylene glycol and anhydrous ethanol were mixed by ball milling to obtain a Si-based tape casting slurry; S2. Al2O3 powder, C powder, Yb2O3 powder, polyethylene glycol butyral, polyethylene glycol and anhydrous ethanol were mixed by ball milling to obtain Al2O3-C casting slurry; S3. After the Si-based tape casting slurry is subjected to a tape casting process in a mold, an n×m matrix is obtained. A Si-based ceramic sheet with circular holes; filling the Al2O3-C tape-casting slurry into the circular holes of the Si-based ceramic sheet to obtain a Si-Al2O3-C composite ceramic sheet; S4. Place the Si-Al2O3-C composite ceramic sheet into a gas pressure sintering furnace, raise the temperature to 800-1000°C under vacuum, then introduce a mixed gas of N2 and H2, then raise the temperature to 1320-1380°C and keep it for 2-3 hours for nitridation treatment, then introduce 4-6MPa flowing N2, raise the temperature to 1600-1800°C and keep it for 3-4 hours, then lower the temperature to 800-1000°C, and after it is naturally cooled to room temperature, obtain the AlN / Si3N4 composite ceramic substrate.
8. The method for preparing the AlN / Si3N4 composite ceramic substrate according to claim 7, characterized in that: The casting process conditions described in step S3 are: casting belt speed is 0.3-3 m / min; green body thickness is 0.3-0.7 mm; drying temperature is 60-80° C.; and drying time is 3-5 h.
9. The method for preparing the AlN / Si3N4 composite ceramic substrate according to claim 7, characterized in that: In step S4, the rate of heating to 800-1000°C is 18-25°C / min, the rate of heating to 1320-1380°C is 15-18°C / min, and the rate of heating to 1600-1800°C is 8-12°C / min.
10. Application of the AlN / Si3N4 composite ceramic substrate according to any one of claims 1 to 6 in the fields of automotive electronics or aerospace.
Citation Information
Patent Citations
High-performance silicon nitride ceramic and preparation method and application thereof
CN109400176A
Preparation method of high-performance silicon nitride porous ceramic
CN109942310A
Black aluminum nitride ceramic shell for 3D sensor and preparation method of black aluminum nitride ceramic shell
CN114195523A
Substrate, preparation method and application
CN116410002A
Seramic material component and manufacturing method thereof
KR101567311B1